(untitled) (Research, Society and Development, 2021)
This work aims to know the relationship between TTTs (Travestis, Transsexual and Transgenders) and the school environment, and tries to identify how this relationship contributes to the exit of TTTs from educational institutions. The research has a qualitative and quantitative approach, predominating the qualitative, following two types of typologies, descriptive and explanatory. Thus, a questionnaire was used as an instrument to collecting data, disseminated through social media, seeking to identify school experiences of this community. As results, we obtained the contribution of eight participants, enabling the selection of relevant speeches for the discussion of this study. We concluded their school daily life, which should be an environment of inclusion and acceptance, has often become hostile, contributing to school evasion, and therefore it is urgent this topic to be constantly present in academic discussions, going through the licentiate courses toward Basic Education, in an attempt to transform the sad reality that surrounds us, as a society and as humans.